Design and Construction of a Urinalysis Instrument for Early Diagnosis of Disease Using TCS3200 Color Sensor and pH E-201C Based on the Internet of Things - Nahdya Afroe (Department of Physics, Universitas Negeri Padang, 2026)
Health is one of the most important things in life, which is why there have been many scientific discoveries in the form of medicines, medical devices, and new inventions in the field of health. Despite advances in health technology, health challenges remain a global issue, especially those related to diseases of the urinary tract and kidneys. Therefore, this study aims to detect diseases early through urine color and pH analysis using a TCS3200 sensor and an E-201C pH sensor. This device is designed to detect several diseases, namely dehydration, kidney stones, kidney failure, and urinary tract infections. The method used is engineering research, which includes hardware and software design, prototype development, and testing of the research device. The measurement results are displayed on an LCD and the Blynk application via NodeMCU ESP32. The test results show that the color sensor is able to classify urine color accurately, while the pH sensor has an average accuracy of 99.90% and a precision of 99.40%.